Clusteroluminescence from Cluster Excitons in Small Heterocyclics Free of Aromatic Rings. Issue 7 (11th February 2021) - He, Benzhao; Zhang, Jing; Zhang, Jianyu; Zhang, Haoke; Wu, Xiuying; Chen, Xu; Kei, Konnie H. S.; Qin, Anjun; Sung, Herman H. Y.; Lam, Jacky W. Y.; Tang, Ben Zhong
Abstract: The study of nonconventional luminescence is important for revealing the luminescence of natural systems and has gradually drawn the attention of researchers in recent years. However, the underlying mechanism is still inexplicable. Herein, the luminescence behavior of two series of simple, heteroatom‐containing small molecules without aromatic rings, i.e., maleimide and succinimide derivatives, are studied to gain further mechanistic insight into the nonconventional luminescence process. It has been unveiled that all the molecules exhibit bright and visible luminescence in concentrated solution and solid state and the formation of clusters is the root cause for such behaviors, which can effectively increase the possibility of both the nonradiative n– π * and favorable π – π * transitions and stabilize the excitons formed in the excited state. The distinctive luminescent phenomena and intriguing mechanism presented in this work will be significant for understanding the mechanism of clusteroluminescence and provide new strategies for the rational design of novel luminescent materials. Abstract : Through systematic and comprehensive study on the luminescent performance of maleimide and succinimide derivatives, it has been unveiled that the formed clusters of these systems can effectively increase the possibility of the traditionally nonradiative n– π * transition and stabilize the excitons in the excited state to facilitate the emission.